Life's worth : the case against assisted suicide - Dyck, Arthur J., 1932- (Grand Rapids, Mich.: William B. Eerdmans Pub. Co., 2002)
In this book Arthur J. Dyck shows there are solid moral and practical bases for the existing laws against assisted suicide. Over the course of four interconnected arguments, Dyck takes readers from a basic concern for human suffering--the main focus of those who support assisted suicide--to the deeper truths of life's inherent worth. Dyck begins by examining the arguments of some physicians, moral philosophers, and theologians for making assisted suicide available. He also discusses the alternative practice of "comfort-only care", explaining why it differs morally from assisted suicide and euthanasia. Dyck then explores and defends the moral structure underlying the West's long tradition of homicide law as well as current law against assisted suicide and euthanasia--laws designed to protect both freedom and human life. Finally, Dyck shows that the moral structure undergirding our system of law is compatible with the views of Christianity, and he points to certain Christian beliefs that provide comfort and hope to those who are suffering, dying, or experiencing the death of loved ones. Throughout the book, Dyck staunchly maintains that assisted suicide is unacceptable in any and all circumstances. The practice denies terminally ill patients the possibility of recovery and robs them of the chance to rethink the meaning of their lives or to achieve spiritual growth. Furthermore, because it undermines the shared moral structure that makes community possible, assisted suicide bodes ill for society as a whole.
Responding to suffering : physician-assisted suidide versus comfort-only care -- Physician-assisted suicide versus comfort only care : do they differ morally in significant ways? -- The moral structure of life's worth and protection -- Christian morality and natural morality in law and public policy.
Includes bibliographical references and index.
Keywords: Assisted suicide -- Moral and ethical aspects; Assisted suicide -- Religious aspects -- Christianity; Christian ethics; Suicide, Assisted -- Ethics; Christianity; Palliative treatment -- Ethics; Political planning; Political planning; Value of Life